Vibrant Children's Library in the Digital Era - Gupta, N.K. (INDIAN EDUCATIONAL REVIEW, 2012)
The book highlights the importance of learning during the process of education from pre-school to higher secondary school. It has linked it to school education, school library as a centre of learning, live workshop and the quality of education. It has also shown the role that books play in Continuous and Comprehensive Evaluation (CCE). The importance of reading habits has been stressed among children in the book. Organising various books-related activities is central point of the book. The book also gives a brief outline on children’s literature and salient features of a good children’s book. The book is divided into 12 chapters. The introductory chapter explains the best ways to improve the quality of education by making it respond to the demands of the society to usher in social change, development and do away with the outdated social practices. This chapter also explains education as a social process, where participation of community in the education process has been shown as pre-condition to knowledge, which has been said to be created by the interaction of knower and knowee. Organisation of knowledge includes knowledge creation, knowledge accumulation and knowledge dissemination.